Lifecycle profit analysis of prefabricated multi-active façades. Issue 5 (10th April 2019) - Sundling, Rikard; Olander, Stefan; Wallentén, Petter; Burke, Stephen; Bernardo, Ricardo; Blomsterberg, Åke
Abstract : Purpose: The purpose of this paper is to identify appropriate concepts of multi-active façades for the renovation of multifamily buildings in Sweden and to determine which, if any, are financially viable. Design/methodology/approach: A lifecycle profit (LCP) analysis was used to examine financial viability through a ten-step process, which included identifying concepts, assessing costs and prices, calculating the LCP and performing sensitivity analysis. Two existing buildings – one low rise and the other high rise – were used as reference models. Findings: The findings were contradictory. Implementing any of the multi-active façade concepts on the high-rise building would be financially beneficial. The opposite was, however, the case for the low-rise building. Two factors causing this contradiction have been identified: the façade material before renovation and the size of the building. Research limitations/implications: The study is limited to two case buildings situated in Sweden; however, similar buildings represent a significant amount of the existing building stock. Part of the purpose of the study is also to investigate the merits of LCP analysis to evaluate energy-efficient retrofitting. The study implicates the benefits and pitfalls of LCP analysis needed to be considered by researchers and practitioners alike. Originality/value: The research findings contribute to the understanding of energy-efficient retrofitting of existing multifamily buildings based on prefabricated multi-active façade concepts.